Fungal and mycotoxin contamination of herbal raw materials and their protection by nanoencapsulated essential oils: An overview. (January 2022) - Singh, Bijendra Kumar; Tiwari, Shikha; Maurya, Akash; Kumar, Susheel; Dubey, Nawal Kishore
Abstract: Presently, consumption of herbal raw materials (HRMs) has been an emerging concern owing to therapeutic potential against broad range of human diseases. However, there are various cases available reporting the fungal and mycotoxin contaminations. These HRMs after collection undergo severe extent of deterioration, leading to degradation of their active principles. Different chemical preservatives have been frequently used to protect HRMs from fungal and mycotoxin contamination, however, their indiscriminate use could lead to adverse effects on human health and environment due to residual toxicity. The use of essential oils (EOs) based formulations has been recommended as a green alternative of synthetic preservatives having greater safety profile and biodegradable nature. Nanoencapsulation maintains the stability of EOs and facilitate the controlled delivery with improvement in maintenance of bioactive principles of HRMs against fungal and mycotoxin mediated biodeterioration to boost pharmaceutical sectors. This review summarizes the pharmacological properties of some HRMs, the extent of degradation by fungal and mycotoxin contamination, preservation through nanoencapsulated EOs, mode of action, patenting of EOs as preservatives, and finally future opportunities to mitigate the associated problems. Highlights: Importance of Herbal raw materials (HRMs) in disease prevention. Fungal and mycotoxin contamination of medicinally important HRMs. Essential oil (EOs) as inhibitor of fungal infestation and mycotoxin biosynthesis. Mode of action of EOs against fungal growth and mycotoxin production. Nanoencapsulation technology as novel approach for protection of HRMs.